2015
DOI: 10.1016/j.idcr.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis in a patient with systemic lupus erythematosus

Abstract: Visceral leishmaniasis is an infection with an insidious and disabling course caused by parasites of the genus Leishmania. In Europe, it is mostly associated with HIV infection. Systemic lupus erythematosus and its treatment are associated with increased risk of infection, neoplastic and concomitant autoimmune disorders. The association of these diseases may go unnoticed.A 60 year-old Caucasian woman with lupus presented with a one-year history of fever, malaise, weakness and weight loss. The highlights on phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the systematic literature review by Santana et al reported in 2015, there were 10 cases in which SLE and VL coexisted and mimicked SLE exacerbation, and 18 cases in which VL led to false suspicion of SLE. The only case from Turkey in this review is a VL case mimicking SLE by Tunccan et al 1,11 In our literature review, we found several more case reports, one from Turkey (the second case reported from Turkey is also a VL case mimicking SLE) 12–15 . In other words, although Turkey is among the endemic countries for leishmaniasis, the case presented here is the first reported case of VL in a lupus patient in Turkey.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In the systematic literature review by Santana et al reported in 2015, there were 10 cases in which SLE and VL coexisted and mimicked SLE exacerbation, and 18 cases in which VL led to false suspicion of SLE. The only case from Turkey in this review is a VL case mimicking SLE by Tunccan et al 1,11 In our literature review, we found several more case reports, one from Turkey (the second case reported from Turkey is also a VL case mimicking SLE) 12–15 . In other words, although Turkey is among the endemic countries for leishmaniasis, the case presented here is the first reported case of VL in a lupus patient in Turkey.…”
Section: Discussionmentioning
confidence: 48%
“…case from Turkey in this review is a VL case mimicking SLE by Tunccan et al 1,11 In our literature review, we found several more case reports, one from Turkey (the second case reported from Turkey is also a VL case mimicking SLE). [12][13][14][15] In other words, although Turkey is among the endemic countries for leishmaniasis, the case presented here is the first reported case of VL in a lupus patient in Turkey.…”
Section: Ta B L E 2 Laboratory Parameters and Treatment Of The Patien...mentioning
confidence: 96%
“…The onset of visceral Leishmaniasis can be acute and hard to make; anyway, no delay is allowed for treatment to prevent a potentially fatal evolution [ 18 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…11 In Europe, L-AMB is recommended as first-line treatment, and as described in the literature, the patient became afebrile and asymptomatic within the first week. 15 A prolonged regime was provided as an option due to the patient's long-term immunosuppression and overall poor clinical condition.…”
Section: Discussionmentioning
confidence: 99%